2019
DOI: 10.1186/s13014-019-1407-9
|View full text |Cite
|
Sign up to set email alerts
|

The preliminary results of proton and carbon ion therapy for chordoma and chondrosarcoma of the skull base and cervical spine

Abstract: PurposeTo evaluate the short-term outcomes in terms of tumor control and toxicity of patients with skull base or cervical spine chordoma and chondrosarcoma treated with intensity-modulated proton or carbon-ion radiation therapy.MethodsBetween 6/2014 and 7/2018, a total of 91 patients were treated in our Center. The median age was 38 (range, 4–70) years. Forty-six (50.5%) patients were treated definitively for their conditions as initial diagnosis, 45 (49.5%) patients had recurrent tumors including 14 had prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 27 publications
0
35
0
1
Order By: Relevance
“…Carbon ions with high linear energy transfer cause hardly reparable complex DNA double-strand break that may overcome the radioresistance of tumor cells [ 147 ]. Both proton and carbon ion radiotherapy provide reasonable local control and patients’ survival rates with acceptable toxicity [ 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ]. There is one ongoing prospective randomized phase III clinical trial that aims to compare the local efficacy of proton and carbon ion therapy in patients with low and intermediate-grade CHSs of the skull base (NCT01182753).…”
Section: Radiotherapy In Chondrosarcomamentioning
confidence: 99%
“…Carbon ions with high linear energy transfer cause hardly reparable complex DNA double-strand break that may overcome the radioresistance of tumor cells [ 147 ]. Both proton and carbon ion radiotherapy provide reasonable local control and patients’ survival rates with acceptable toxicity [ 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ]. There is one ongoing prospective randomized phase III clinical trial that aims to compare the local efficacy of proton and carbon ion therapy in patients with low and intermediate-grade CHSs of the skull base (NCT01182753).…”
Section: Radiotherapy In Chondrosarcomamentioning
confidence: 99%
“…When the tumor can not be removed completely or the cutting edge is positive, radiotherapy is an important adjuvant therapy (Shah et al 2016). Proton or carbon ion-ion therapy is also effective for the unresectable or incomplete resection of UPS, but due to the limited number of postoperative radiotherapy cases of renal UPS, there is still a lack of large sample data (Demizu et al 2017;Guan et al 2019). Because of the small number of cases and a short follow-up period, the effect of chemotherapy after renal UPS is not clear (Gronchi et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Also, particle beams with higher linear energy transfer (e.g., carbon ion) produces significantly higher biological effectiveness as compared with photon beams (23), a clear advantage for radioresistant histologies such as most subtypes of sarcomas. Clinical data from several retrospective studies showed that PBRT could achieve favorable disease control for head and neck sarcomas or base of skull tumors, including chordoma and chondrosarcoma, even in patients with unresected or recurrent diseases (24)(25)(26)(27)(28)(29). In our previous studies, PBRT for head and neck sarcomas, including those involving skull base, produced effective tumor controls, and overall survivals in both primary and recurrent patients; the 1/2-year OS and LRFS for the entire cohort were 92.9/90.0 and 88.4/78.9%, respectively (24,25).…”
Section: Discussionmentioning
confidence: 99%